Beauty, job tasks, and wages: A new conclusion about employer taste-based discrimination - Todd R. Stinebrickner; Ralph Stinebrickner; Paul Sullivan (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
We use novel data to show that the beauty wage premium exists only in jobs where attractiveness is plausibly a productive characteristic. A large premium exists in jobs that require substantial amounts of interpersonal interaction, but no such premium exists in jobs that require working with information and data. This is inconsistent with employer taste-based discrimination, which would favor attractive workers in all jobs. Our unique task data address concerns that measurement error in the importance of interpersonal tasks may bias results towards employer discrimination. Our conclusions are in stark contrast to all previous research that uses a similar approach.
Keywords: 330